2014
DOI: 10.1002/asi.23112
|View full text |Cite
|
Sign up to set email alerts
|

The communicative ecology of Web 2.0 at work: Social networking in the workspace

Abstract: Social media have transformed social interactions and now look set to transform workplace communications. In this exploratory study, we investigate how employees use and get value from a variety of social networking technologies. The context of this research is 4 software firms located in China. Notwithstanding differences in corporate attitudes toward social networking, we identify common themes in the way Web 2.0 technologies are leveraged as value is created by employees at all levels. We draw on the commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 41 publications
1
40
0
Order By: Relevance
“…Developers were found to make use of multiple social media for a range of information sharing requirements, from supporting updates and discussions (via Yammer or the forum) to archiving technical knowledge (in the wiki), which one tool would have struggled to satisfy. Subsequently the availability of different tools allowed developers to create their own communication ecologies (Davison et al, 2014). This supports findings from earlier studies that determined that users can make sense of multiple social media tools (eg, Jarrahi & Sawyer, 2013;Turner et al, 2010).…”
Section: The Implications Of Multiple Social Media For Coherencesupporting
confidence: 82%
See 2 more Smart Citations
“…Developers were found to make use of multiple social media for a range of information sharing requirements, from supporting updates and discussions (via Yammer or the forum) to archiving technical knowledge (in the wiki), which one tool would have struggled to satisfy. Subsequently the availability of different tools allowed developers to create their own communication ecologies (Davison et al, 2014). This supports findings from earlier studies that determined that users can make sense of multiple social media tools (eg, Jarrahi & Sawyer, 2013;Turner et al, 2010).…”
Section: The Implications Of Multiple Social Media For Coherencesupporting
confidence: 82%
“…They highlighted that a single tool cannot satisfy all employee needs, and how differences emerged between groups; for instance, people who worked in R&D were more open to use social media in their work, compared to those with less technical tasks (eg, finance). In a similar fashion, Davison et al (2014) found a mixture of competition and complement; in some cases, social media had completely replaced existing technologies, whilst it in other cases acted as a complement to more ingrained technologies (eg, email). Muller et al (2012) noted how social media were appropriated differently across groups when creating and using shared resources and forming relationships.…”
Section: Ecological Approachmentioning
confidence: 94%
See 1 more Smart Citation
“…Social technologies contribute to horizontal and vertical communication in organizations (Davison et al, 2014;Tormo-Carbo, Segui-Mas, & Oltra, 2014) and serve as collaborative tools to accelerate group formation and escalate group scope and influence (Leftheriotis & Giannakos, 2014;Lin & Lu, 2011;Zhao & Rosson, 2009). Extent research refers to social media's role as vehicle for informal communication in the workplace, representing 'an online water-cooler' (Cao, Vogel, Guo, Liu, & Gu, 2012;Dimicco et al, 2008;Skeels & Grudin, 2009).…”
Section: In-group Communicationmentioning
confidence: 99%
“…Social media changes the way how people communicate with each other in personal and professional lives [19]. The latest ubiquitous form of social media based on mobile technologies allows people to stay connected anytime and anywhere [7].…”
Section: Introductionmentioning
confidence: 99%